THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT TELKOM ACCESS GAHARU MEDAN - Salman Farisi; Deby Paramita (CERED Indonesia Institute, 2020)
The purpose of this research is to know some of the things that the effect of transformational leadership on employee performance, the effect of motivation on employee performance, and the effect of transformational leadership and motivation on employee performance at PT. Telkom Access Gaharu Medan. In this research on approach used through an associative approach. The sample used in this research is the simple random sampling teachnique, which is the sampling taken when the first sample was random. The data collection techniques used in the research are questionnaires and data analysis teaches using SPSS (Statistical Package For The Social Sciences) to test the three hypotheses advanced in the research. Research shous that (1) the effect of transformational leadership on the employee performance are positive and significant